Literature Review of Digital Recruitment: How Effective is Artificial Intelligence in Selecting People? - Dahniar Nur Amalina; Siskha Nur Khasanah; Dandy Yuliansyah; Syarifa Hanoum (Syntax Idea)
The use of artificial intelligence in recruitment can help select candidates according to company standards through a simple, effective, and efficient process. This paper investigates how the AI implementation in the traditional recruitment process transform into the AI-based recruitment and its impact on recruitment processes. We use systematic literature review and content analysis to obtain information regarding research gaps, research limitations, and future research opportunities. We analyze 35 articles collected between 2008 and 2022 showing that AI has several benefits, including increasing the interest of candidates to apply for jobs, increasing efficiency and timeliness, reducing recruitment costs, obtaining the best candidates, and reducing bias in the recruitment process